Adenine Nucleotide and Nicotinamide Adenine Dinucleotide Measurements in Plants. Issue 3 (25th August 2020) - Zhang, Youjun; Krahnert, Ina; Bolze, Antje; Gibon, Yves; Fernie, Alisdair R.
Abstract: As the principal co‐factors of many metabolic pathways, the measurement of both adenine nucleotides and nicotinamide adenine dinucleotide provides important information about cellular energy metabolism. However, given their rapid and reversible conversion as well as their relatively low concentration ranges, it is difficult to measure these compounds. Here, we describe a highly sensitive and selective ion‐pairing HPLC method with fluorescence detection to quantify adenine nucleotides in plants. In addition, nicotinamide adenine dinucleotide is a crucially important redox‐active substrate for multiple catabolic and anabolic reactions with the ratios of NAD + /NADH and NADP + /NADPH being suggested as indicators of the general intracellular redox potential and hence metabolic state. Here, we describe highly sensitive enzyme cycling−based colorimetric assays (with a detection limit in the pmol range) performed subsequent to a simple extraction procedure involving acid or base extraction to allow the measurement of the cellular levels of these metabolites. © 2020 The Authors. Basic Protocol 1 : Preparation of plant material for the measurement Basic Protocol 2 : Measurement of ATP, ADP, and AMP via HPLC Basic Protocol 3 : NAD + /NADP + measurements Basic Protocol 4 : NADH/NADPH measurements Basic Protocol 5 : Data analysis and quality control approaches